SMS for sexual health: A comparison of service types and recommendations for sexual health text message service providers. (March 2017) - Willoughby, Jessica Fitts; Muldrow, Adrienne
Objectives: Text message–based interventions may provide sexual health information to young people through a number of service types, from sending information on a regularly scheduled timeline, to providing an automated menu, to allowing young people to connect directly with health educators. While such service types exist, it is not clear which features young adults feel are most effective at allowing them to engage with sexual health information. Design: This study used a mixed-methods design (survey and focus groups) to assess perceptions of three types of sexual health text message services with young adults, a population particularly at risk of negative sexual health outcomes. Setting: College students from the US Pacific Northwest participated in the project. Method: Participants heard about three sexual health text message services, completed questionnaires and discussed each type. Focus groups were gender-separated. Results: Participants reported that services that allowed them to connect with a health educator would be highly useful, but automated services would be beneficial in bringing new topics to their attention. Participants perceived the purpose of the service types as different and felt each could be a useful resource, depending on the situation. Regardless of service type, participants wanted to personalise their experience. Participants wanted messages tailored to them and options to interact with the systems, from influencing topic selection to message timing. Conclusion: Each of the service types can be useful for young adults. Young adults perceive services that provide the opportunity to tailor information and interact with the system as beneficial.